Light fragment yields from central Au+Au collisions at 11.5A GeV/c - Barrette, Jean; Stachel, Johanna; Wessels, Johannes P. (Physical review. C, Nuclear physics, 2000)
Inclusive double differential multiplicities of deuterons, 3H, 3He, and 4He measured by E877 for 11.5AGeV/c Au+Au collisions at the Brookhaven’s Alternating Gradient Synchrotron (AGS) are presented. Light fragments at beam rapidity are measured for the first time at AGS energies. Beam rapidity deuteron and 4He yields and transverse slope parameters are found to be strongly dependent on the impact parameter, and the shape of the deuteron spectra is not consistent with that expected for a simple thermal distribution. The deuteron yields relative to proton yields are analyzed in terms of a simple coalescence model. While results indicate an increase in source size compared to collisions of lighter systems at the same energy, they are inconsistent with a simple coalescence model reflected by a rapidity dependence of the coalescence parameter Bd. A new approach utilizing an expanding thermalized source combined with a coalescence code is developed for studying deuteron formation in heavy-ion collisions. The strong dependence of deuteron yields on collective motion implies that deuteron yields relative to those of protons can be used for constraining source parameters.